Analisis Lean Six Sigma Perbekalan Farmasi di Gudang Farmasi RS PMI Bogor Tahun 2013 - Putri, Elizabeth Indah Prihanti Soetardi (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2015)
This pharmacy service study was conducted at PMI Hospital which has low inventory turnover. Lean six sigma method was used in action research approach with focus on pharmacy distribution and inventory storage. The study analyzed distribution process, material request period, buffer stock, quantity of demand, material request conditions, ROP, pharmacy indicator, adjusting stock quantity, expired material and medicines, expired item management, material handling in warehouse. The low inventory turnover was caused by poor understanding of inventory stock by pharmacy personnel. The results showed that deviation standard for pharmacy item request was 54,8 and deviation standard for completeness of pharmacy item was 50,4, and the value of Six Sigma Defect Per Million Opportunities was 0,09, the pharmacy item distribution process was 47,6% that means it was non value added. The contributing factors were the long item request time, inaccuracy estimation, lack of understanding of request estimation, inaccuracy documentation, bottleneck on distribution process at pharmacy installation, no evaluation on inventory turnover, no detail procedure. Technology on inventory system was not optimal used due to no standard of minimum-maximum level of each pharmacy item and the storage and warehouse management standard was not implemented yet.